Inventarisasi Jenis Capung (Odonata) Pada Areal Persawahan Di Desa Pundenarum Kecamatan Karangawen Kabupaten Demak - Rizal, Samsul; Hadi, Mochamad (Bioma : Berkala Ilmiah Biologi, 2015)
Paddy fields is one of the important ecosystem that support human life because here produced rice that is the main food to the human. Besides, paddy field ecosystem also have many diversity of insect, including dragonfly (Odonata). Dragonfly (Odonata) is one of the insect that used to be a predators to the pests in the paddy fields, such as Chilo sp and Nilaparvata lugen. The study on dragonfly was conducted in Pundenarum village, Karangawen, Demak. The objectives of this study is to identify the odonata specieses that lived in paddy field. Inventory of odonata specieses done with field by field method and direct catch using insect net. The result of this study is that 5 specieses of odonata were identifiedÂ  in paddy field, i.e: Orthetrum sabina, Crocothemis servillia, Pantala flavescens, Agriocnemis femina dan Agriocnemis pygmea. The odonata specieses that identified is part of 2 family, i.e: Libellulidae and Coenagrionidae. It is also found that all species is part of the suborder Anisoptera (dragonfly) and Zygoptera (damselflies). Key word : dragonfly, Odonata, inventory, paddy field.